2021
DOI: 10.3390/f12121634
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation, Characterization, and Conservation of Phytophthora cinnamomi-Tolerant Holm Oak Mature Trees

Abstract: Holm oak populations have deteriorated drastically due to oak decline syndrome. The first objective of the present study was to investigate the use of axillary budding and somatic embryogenesis (SE) to propagate asymptomatic holm oak genotypes identified in disease hotspots in Spain. Axillary budding was achieved in two out of six tolerant genotypes from the south-western region and in two out of four genotypes from the Mediterranean region. Rooting of shoots cultured on medium supplemented with 3 mg L−1 of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 84 publications
2
20
0
Order By: Relevance
“…Although plant conversion from somatic embryos in many hardwoods is considered an important bottleneck [ 15 ], in the present study plants from four independent transgenic lines were successfully recovered by applying the protocols previously described for holm oak somatic embryos [ 9 , 50 ]. The in vitro behaviour and growth of these transgenic plants were not affected by overexpression of the Cast_Gnk2-like gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although plant conversion from somatic embryos in many hardwoods is considered an important bottleneck [ 15 ], in the present study plants from four independent transgenic lines were successfully recovered by applying the protocols previously described for holm oak somatic embryos [ 9 , 50 ]. The in vitro behaviour and growth of these transgenic plants were not affected by overexpression of the Cast_Gnk2-like gene.…”
Section: Discussionmentioning
confidence: 99%
“…P. cinnamomi is one of the most destructive and widely spread oomycetes throughout the world, and it has been associated with the death of numerous different plant species, including many woody species [ 8 ]. To date, there are no efficient chemical methods available for controlling this oomycete [ 9 ]. The most effective means appears to be the afforestation of affected zones with genotypes that are tolerant to P. cinnamomi .…”
Section: Introductionmentioning
confidence: 99%
“…Also, during pathogen attack the phenylpropanoid pathway genes were found to be overexpressed, resulting in increasing activities and accumulation of various phenolic compounds (Yadav et al, 2020 ). More recently, our group demonstrated that axillary shoots from tolerant holm oak genotypes established in vitro had higher total phenol content than other susceptible genotypes (Martínez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a national program for breeding and conservation of cork-and holm oak genetic resources against the decline syndrome has also been established. For exploiting all the genetic variability existing in natural populations, superior genotypes should be vegetatively propagated, but this task is hampered by the low rooting capability of oak cuttings, which is even reduced with the aging of the trees (Martínez et al, 2020(Martínez et al, , 2021. In this context, biotechnological tools such as somatic embryogenesis constitute an interesting alternative allowing clonal propagation of holm oak adult trees (Blasco et al, 2013;Barra-Jiménez et al, 2014;Martínez et al, 2017Martínez et al, , 2020Martínez et al, , 2021, although acclimatization of generated plants needs to be improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation